Simbolisme Ragam Hias Sisik Batik Demak - Adisukma, Wisnu (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
Sisik ornament on Demak’s Batik is considered as cultural form, artifact that is contains self representation discourse which is framed by cultural ideographic aspect. However, Demak’s Batik vanished for hudred years from Demak society and emerged in 2006. Therefore, there is cultural communication that vanished in Demak society, particularly it is connected to meaning or value system which is contained in sisik ornament Demak’s Batik for life of Demak’s society. Therefore, it is essential to observe about sisik ornament as particular motif of Demak and the symbolism of sisik ornament on Demak’s Batik and the implication to Demak’s life society. The approach that is used is cultural approach. This approach observes sisik ornament on Demak’s Batik as culture and as part that is never divide, even become the cultural center of Demak’s society.Keywords: Demak’s Batik, Sisik Ornament, Simbolism